Two interviews with Berthold Lubetkin, April‑May 1974 - Tim Benton (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Berthold Lubetkin (1901–1990) was a leading exponent of modern architecture in England in the 1930s. After continuing his practice briefly after the war, he dropped out of public view, preferring to manage his farm in Gloucestershire. Through the good agencies of the Senior Producer for Radio at the Open University, I was able to interview him and draw him back into public discourse. The two radio talks were transmitted on the BBC between 1975 and 1983.